Investigation of fatigue strength of repaired glass/epoxy composites using resin injection method assisted by acoustic emission - Faraz Haddad; Atabak Pourdadash Fardnam; Mehdi Ahmadi Najafabadi (Advances in Mechanical Engineering, 2025)
Graphical abstract